Host- and Fusarium-Adapted Bacterial Consortia Alter Microbial Community Structures in Arabidopsis Roots and Suppress Fusarium oxysporum - Enoch Narh Kudjordjie; Rumakanta Sapkota; Mogens Nicolaisen (Phytobiomes Journal, 2024)
The plant-associated microbiota confers beneficial traits to the plant host by promoting growth and preventing disease. However, it is not fully understood how the host and its associated microbiota interact with pathogens. In this work, we studied how the host plant modulates its associated microbiome to suppress disease. For this, we used two Arabidopsis thaliana lines with different host responses to Fusarium oxysporum f. sp. mathioli (FOM). We isolated bacterial consortia (BCs) from FOM-infected or healthy host plants of the two lines of Arabidopsis and studied their effect on the root-associated microbiota and FOM progression in the following generations of Arabidopsis plants. Root bacterial and fungal communities were profiled using 16S ribosomal RNA and internal transcribed spacer amplicon sequencing, respectively, while quantitative PCR was used for assessment of FOM quantities in shoots of Arabidopsis. Host- or pathogen-adapted BCs significantly reduced FOM quantities in shoots of both the resistant Col-0 and the susceptible Ler-0 Arabidopsis lines. Several bacterial taxa, including Chthoniobacter, Bacillus, Chryseobacterium and Actinoplanes negatively correlated with FOM, suggestive of an antagonistic effect. Furthermore, both host- and pathogen-adapted BCs significantly affected community composition with distinct differentially abundant taxa and co-occurrence network structures. Taken together, our findings suggest that using a subcommunity selection approach is a potential route for exploiting plant-associated rhizosphere microbiomes for engineering disease resilient microbiomes. [Graphic: see text] Copyright © 2024 The Author(s). This is an open access article distributed under the CC BY 4.0 International license.